Elemental Sulfur Nanoparticles Chemically Boost the Sodium Storage Performance of MoS2/rGO Anodes. Issue 5 (27th August 2018) - Xu, Zhanwei; Fu, Hao; Yao, Kai; Shen, Xuetao; Li, Zhi; Fu, Licai; Huang, Jianfeng; Li, Jiayin
Abstract: The critical role of sulfur nanoparticles in stabilizing MoS2 supported on reduced graphene oxide as anode material for sodium‐ion batteries is discovered. The MoS2 supported on reduced graphene oxide decorated with sulfur particles (∼50 nm) is in‐situ synthesized using an ammonium molybdate/graphene oxide preform and sublimed sulfur through a facile chemical vapor deposition process in a tube furnace with 2 temperature‐controlled zones. Although the sulfur particles show no positive effect when the material is tested as anode for Li‐ion batteries, they significantly improve the Na storage performance in terms of both, total specific capacity and cycle life. A stable high capacity of 580 mAh g −1 and an extremely low capacity fade of 94 μAh g −1 cycle −1 make the designed assembly one of the best‐performing MoS2 ‐based anode materials for sodium‐ion batteries so far. The post‐cycling analysis reveals that the elemental sulfur nanoparticles play two roles: during the intercalation of Na in‐between the layers of MoS2 (above 1.0 V), they function as blockers and inhibit the aggregation of MoS2 ; in the conversion reaction stage, the sulfur nanoparticles chemically participate in the Na storage process by forming Na2 S5 ‐rich compounds, which eventually improve the reversibility of the conversion reaction and thereafter the cycling performance. Abstract : Small decoration with big effect ! A MoS2 reduced graphene oxide composite decorated with sulfur particles (∼50 nm) is in‐situ synthesized using an ammonium molybdate/graphene oxide preform and sublimed sulfur. The sulfur nanoparticles chemically participate in the Na storage process by forming Na2 S5 ‐rich compounds, improving the reversibility of the conversion reaction and thereby, the cycling stability.